Perkembangan Motorik Anak Usia Dini Dengan Metode Bermain di TPA Al-Ikhsan Desa Belantaraya Kecamatan Gaung - Hasan Fauzi; Yusnita Yusnita; Rita Kencana; Sutria Ningrum; Nova Adi Kurniawan (STAI Auliaurrasyidin Tembilahan, 2022)
Early childhood is those who are at the age of 0-6 years. They are at a very rapid stage of growth and development, both physically and psychologically. They learn in their own way. They have two aspects of development, namely biological and psychological. This is quantitative descriptive research, which was conducted at the TPA Al-Ikhsan, Belantaraya, Indragiri Hilir, Riau. The subject of this research was 23 students of TPA Al-Ikhsan. The data in this study was taken by using tests of early childhood motor skills, and documentation. They were then analyzed by using P= ×100% to see the motor skills of children. The results presented that the students’ motoric skills were at 54,10% in the category of developed as expected (DE). On the other hand, the students’ motoric skills developed as expected.